Elimination of Onchocerca volvulus Transmission in the Huehuetenango Focus of Guatemala. (23rd August 2012) - Cruz-Ortiz, Nancy; Gonzalez, Rodrigo J.; Lindblade, Kim A.; Richards, Frank O.; Sauerbrey, Mauricio; Zea-Flores, Guillermo; Dominguez, Alfredo; Oliva, Orlando; Catú, Eduardo; Rizzo, Nidia
Abstract : In Latin America, onchocerciasis is targeted for elimination by 2012 through twice-yearly mass treatment of the eligible population with ivermectin. In Guatemala, two of the four historical endemic foci have demonstrated elimination of transmission, following World Health Organization guidelines. Using established guidelines ophthalmological, serological, and entomological evaluations were conducted in 2007-8 to determine the transmission status of onchocerciasis in the Huehuetenango focus. The prevalence of Onchocerca volvulus microfilariae in the anterior segment of the eye in 365 residents was 0% (95% confidence interval [CI] 0–0.8%), the prevalence of infection of O. volvulus in Simulium ochraceum among 8252 flies collected between November 2007 and April 2008 was 0% (95% CI 0–0.02%), and the prevalence of antibodies to a recombinant O. volvulus antigen in 3118 school age children was 0% (95% CI 0–0.1%). These results showed transmission interruption; thus, in 2009 mass treatment was halted and posttreatment surveillance began. To verify for potential recrudescence an entomological evaluation (from December 2010 to April 2011) was conducted during the 2nd and 3rd year of posttreatment surveillance. A total of 4587 S. ochraceum were collected, and the prevalence of infection of O. volvulus was 0% (95% CI 0–0.04%). Transmission of onchocerciasis in the Huehuetenango focus has been eliminated.